Factors Influencing Young People's Interest in Becoming Farmers in Langkat District - Rahayu Widya Ningsih; Mhd Buhari Sibuea; Faiz Ahmad Sibuea; Tri Martial (Cita konsultindo, 2025)
This research is motivated by the lack of interest of the younger generation in entrepreneurship in agriculture, it is important to know the factors that can be a driving force for the younger generation to become farmers. The objectives of the study were to determine or analyze the profile of the interest of the younger generation as farmers, analyze the influence of social and economic factors that influence the interest of the younger generation as farmers, analyze the influence of educational and psychological factors that influence the interest of the younger generation as farmers, and analyze the influence of environmental and cultural factors on the interest of the younger generation as farmers. This research was conducted at SMK Swasta Pertanian Pembangunan Putra Jaya Stabat. The research method used in this study is a quantitative approach with the SEM method. To analyze the factors that influence the interest of the younger generation as farmers. The quantitative approach was chosen because of its ability to provide objective and measurable numerical data, as well as its ability to statistically identify patterns and relationships between variables. The results of this study show: 1). The profile of young people's interest in the farming profession at SMK Pertanian Pembangunan Putra Jaya is still low, 2). Social and economic factors have a significant effect on the interest of young people to become farmers. 3). Educational and psychological factors have a significant effect on the interest of the younger generation in the farming profession. And 4). Cultural environmental factors significantly influence the interest of the younger generation to become farmers.